1994
DOI: 10.1109/10.277268
|View full text |Cite
|
Sign up to set email alerts
|

High frequency ultrasonic backscatter from erythrocyte suspension

Abstract: Previous studies have shown that ultrasonic backscattering from red blood cells suspended in saline is proportional to the fourth power of frequency for frequencies below 15 MHz, as predicted by Rayleigh scattering theory. Recently, we have extended the measurements up to 30 MHz, because scattering of ultrasound by red blood cells may no longer be negligible at these frequencies and can affect, to a great degree, the operation of intravascular imaging devices. The experimental results show that the fourth powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
4
15
0
Order By: Relevance
“…This scatterer density is high in blood, and therefore it makes ultrasonic blood characterization difficult. A nonlinear relationship has been found between backscattering power and scatterer concentration in an extremely dense medium (such as blood) [17]. Backscattering is dependent on an acoustic impedance mismatch between the tissue and cell components [12].…”
Section: Introductionmentioning
confidence: 99%
“…This scatterer density is high in blood, and therefore it makes ultrasonic blood characterization difficult. A nonlinear relationship has been found between backscattering power and scatterer concentration in an extremely dense medium (such as blood) [17]. Backscattering is dependent on an acoustic impedance mismatch between the tissue and cell components [12].…”
Section: Introductionmentioning
confidence: 99%
“…Under the condition ka < 1, ultrasound backscattering is not affected by the shape of scatterers [30]. Savery and Cloutier reported that ultrasound backscattering behavior of RBCs as a function of frequency is very similar to Rayleigh scattering below 87 MHz with analytical and semi-analytical models study [31].…”
Section: Resultsmentioning
confidence: 99%
“…The T-matrix formulation for a sphere was used to compare with its experimental results. T mv , an indexed element in the matrix, was defined as the ratio of scattering field coefficients Qmvs to incident field coefficients Qmvi and written as [22]…”
Section: Methodsmentioning
confidence: 99%